Analysis of the effects of cost cutting measures on financial performance: a case of ZETDC - Matongo, Francis T. (Midlands State University, 2017)
The purpose of this research was to investigate the effects of cost cutting measure on financial performance using ZETDC as a case. The research objectives outlined the nature of cost cutting techniques, how cost cutting affect financial performance and challenges faced in the implementation of cost cutting. The descriptive survey research design was used and data was gathered through the use of structured questionnaires and interviews and a total population of 41 employees which included the top management, Accountants, HR and internal auditors was sampled using convenience and purposive sampling. A case study approach was undertaken using both qualitative and quantitative data hence the study is therefore a mixed design approach. The research was designed in a way that allows both field research and secondary sources to be used. Research instruments considered for the purposes of this research are questionnaires which had 88% response rate and interviews which yielded 100% response rate. The data gathered was presented through histograms, bar graphs, pie charts and tables. The data accumulated was analysed using descriptive statistics specifically percentages and mode and rational conclusions were drawn from this. Upon data analysis, it was revealed that ZETDC cost cutting measures positively affects the financial performance in the long run but in the short run the financial woes will worsen before they improve. The recommendations passed by the researcher included the improvement of current cost cutting measures and continuation with the application of the cost cutting measures. The researcher also recommended ZETDC to implement controls so as to make sure that all current cost control procedures and policies are adhered to, budget formulation and introduction of incentives and bonuses for meeting budgets and lastly renegotiating existing transfer prices in contracts agreed with other subsidiaries of ZESA.